2019
DOI: 10.3390/ma12142236
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Fatigue Damage Model of Asphalt Mixture Based on Dynamic Modulus and Residual Strength Decay

Abstract: In order to describe the fatigue damage state of asphalt mixture more reasonably, direct tensile tests of the fatigue and the residual strength under stress levels of 1.00 MPa, 0.50 MPa and 0.25 MPa with five parallel tests were carried out. The trabecular specimens of AC-13C asphalt mixture (25 cm × 5 cm × 5 cm) were manufactured with Styrene-Butadiene-Styrene (SBS) modified asphalt, aggregate basalt and limestone mineral filler. The optimum asphalt-aggregate ratio was 5.2%. The dynamic modulus decay and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…The fatigue stress strength ratio ∆ is served as a fatigue resistance index, with Equation ( 22) defining its formula. ∆ = σ ei σ es (22) where σ ei represents the initial equivalent stress, while σ es represents the equivalent stress at the point of fatigue failure. The formula for equivalent stress is:…”
Section: Unified Characterization Model For Modulus Decay Of Asphalt ...mentioning
confidence: 99%
See 3 more Smart Citations
“…The fatigue stress strength ratio ∆ is served as a fatigue resistance index, with Equation ( 22) defining its formula. ∆ = σ ei σ es (22) where σ ei represents the initial equivalent stress, while σ es represents the equivalent stress at the point of fatigue failure. The formula for equivalent stress is:…”
Section: Unified Characterization Model For Modulus Decay Of Asphalt ...mentioning
confidence: 99%
“…where σ 1 is the first principal stress; σ 2 is the second principal stress; σ 3 is the third principal stress. Equation (22) shows the ratio of the stress level to material resistance during asphalt mixture fatigue testing. Using the ratio ∆, which considers the stress state and loading rate, a normalized fatigue equation is established as follows.…”
Section: Unified Characterization Model For Modulus Decay Of Asphalt ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Mahmoud et al [ 10 ] applied viscoelastic continuum damage theory to simulate the asphalt fatigue properties, and found that there was a good correlation between viscoelastic parameters and anti-fatigue performance of asphalt mixture. Liu et al [ 11 ] found that the residual strength-dynamic modulus coupled model could better describe the fatigue damage evolution law of an asphalt mixture, and the parameter of this coupled model could be obtained by fewer residual strength tests. The fatigue life model of an asphalt mixture based on the definition of damage variable was put forward by Castro et al [ 12 ].…”
Section: Introductionmentioning
confidence: 99%